Development of Canva Application-Based Arabic Learning Media to Improve The Skills of 21st Century Educators - Tomi enramika; Zakiyatunnisa Al Mubarokah; Putri Hardiyanti (PT. Islamic Research Publisher, 2023)
After the COVID-19 pandemic has had a lot of impact on the learning process, all learning activities tend to be dominated by technology. Mastery of technology is a must, including for educators in learning Arabic. The purpose of this study is to explain the development of Arabic learning media in accordance with the demands of the 21st century, as for the skills that must be mastered by educators in the 21st century, namely being able to master the 4Cs which are a means to achieve success in life, while the 4C skills in question are Communication, Collaboration, Critical thinking and Problem Solving, and Creativity and Innovation skills and one of the supporting applications in media making Arabic learning that is appropriate for the 21st century is through the Canva application. The type of research used is a literature study of research results that have been published in national journals and proceedings. The results of the research that using the Canva application can be used in designing attractive Arabic learning media in accordance with the demands of the times so that it will facilitate teachers in the learning process and achieve the learning goals that have been set.